The integration hypothesis: A critical evaluation informed by multilevel meta-analyses of three multinational datasets - Grigoryev, Dmitry; Berry, John W.; Stogianni, Maria; Nguyen, Angela-MinhTu D.; Bender, Michael; Benet-Martínez, Verónica (International journal of intercultural relations, 2023)
The integration hypothesis is the proposal that individuals who engage in both their heritage culture and in the larger society (by using the integration strategy) have better psychological adaptation than those using other strategies (by engaging with only one or neither cultural framework). This hypothesis has received substantial support over the years, but it has been recently contested by Bierwiaczonek and Kunst (2021). In their paper, which contributed new meta-analytic evidence, including some based on longitudinal studies, they argue that there is limited support for the role of acculturation strategies in adaptation and that contextual factors are more important than acculturation strategies for adaptation. Our paper shows that their correlational meta-analysis underestimates the integration-adaptation effect size, and that findings from the longitudinal meta-analysis do not appropriately support their claim. We present empirical findings in support of the integration hypothesis, particularly for positive indicators of adaptation (e.g., life satisfaction, self-esteem), and examine additional moderators using multilevel analyses of three multinational datasets: Nguyen and Benet-Martínez’s (2013) meta-analytic data, the MIRIPS dataset (Berry et al., 2022), and the ICSEY dataset (Berry et al., 2006). As a result, our study represents the largest test of the integration hypothesis to date. We complement these findings with theoretical work, relevant evidence from qualitative studies, and other meta-analyses and narrative reviews. •Largest evaluation of the integration hypothesis to date, covering an extensive three multinational datasets.•Empirical evidence supports a positive association between the integration strategy and adaptation.•Meta-regression analysis identifies moderating factors in the integration-adaptation relationship.•Stronger effect sizes observed for positive indicators of adaptation, such as life satisfaction and self-esteem.